Recursive MDS matrices effective for implementation from Reed-Solomnon codes and direct exponent transformation - Lượng, Trần Thị; Cương, Nguyễn Ngọc; Thọ , Hoàng Đức; Công, Hoàng Anh (Journal of Science and Technology on Information security, 2023)
Abstract— Nowaday, many block ciphers have used MDS matrices for their diffusion layer. However, the MDS matrices are always the components that cause large implementation cost for ciphers. Recursive MDS matrices will help to deal with this problem because they can be the power of a simple Companion matrix that is very sparse. In this paper, the ability to generate different efficient recursive MDS matrices for implementation from an original efficient recursive MDS matrix by direct exponential transformation is shown. These recursives MDS matrices are meaningful in hardware implementation. These matrices can be used in the diffusion layer of some block ciphers and hash functions ciphers and hash functions especially lightweight block ciphers and hash functions to save resources and implementation cost.